Mechanical Thrombectomy for Treatment of Acute Cerebral Infarction due to Distal Medium Vessel Occlusions: A Retrospective Cohort Study - Lihong Zhang; Fanfan Su; Jianhui Zhang; Jia Xu; Manhong Zhao; Di Li; Lin Yin (Brain and Behavior)
ABSTRACT Background Mechanical thrombectomy (MT) is standard of care for acute cerebral infarction (ACI) due to large vessel occlusions. However, its clinical efficacy in patients with ACI due to distal medium vessel occlusions (DMVOs) remains unclear. This study evaluates the efficacy and safety of MT in patients with ACI due to DMVOs. Methods Totally, 306 patients with ACI at a very early stage were assigned into DMVOs‐MT, M1‐MT, and DMVOs‐intravenous thrombolysis (IVT) groups. These groups were compared regarding baseline data, recanalization rate, location of vessel occlusions, number of thrombectomy, first‐pass recanalization, mRS scores, NIHSS scores, 90‐day mRS scores, incidence of adverse events, and mortality. Risk factors for poor prognosis of patients with DMVOs following MT were analyzed. Results DMVOs‐MT and M1‐MT groups showed comparable first‐pass recanalization rates, recanalization rates, and NIHSS score reduction ratios, with marked differences in location of vessel occlusions. Versus DMVOs‐IVT, DMVOs‐MT had increased differences between pre‐ and post‐treatment NIHSS scores and between pre‐treatment NIHSS scores and NIHSS scores at discharge and elevated NIHSS reduction ratios. The poor prognosis rate of DMVOs‐MT group was insignificantly different from that of M1‐MT group but lower than that of DMVOs‐IVT group. Adverse events and mortality incidences were comparable among the three groups. Diabetes, first‐pass recanalization, and pre‐treatment NIHSS scores were independent risk factors for poor prognosis in DMVO patients after MT. Conclusion MT is as effective and safe in patients with DMVOs as in patients with M1 occlusions. In patients with DMVOs, MT has higher efficacy and safety than IVT.